Tissue engineering and regenerative medicine: past, present, and future - Salgado, A. J. (2013)
Tissue and organ repair still represents a clinical challenge. Tissue engineering and regenerative medicine (TERM) is an emerging field focused on the development of alternative therapies for tissue/organ repair. This highly multidisciplinary field, in which bioengineering and medicine merge, is based on integrative approaches using scaffolds, cell populations from different sources, growth factors, nanomedicine, gene therapy, and other techniques to overcome the limitations that currently exist in the clinics. Indeed, its overall objective is to induce the formation of new functional tissues, rather than just implanting spare parts. This chapter aims at introducing the reader to the concepts and techniques of TERM. It begins by explaining how TERM have evolved and merged into TERM, followed by a short overview of some of its key aspects such as the combinations of scaffolds with cells and nanomedicine, scaffold processing, and new paradigms of the use of stem cells for tissue repair/regeneration, which ultimately could represent the future of new therapeutic approaches specifically aimed at clinical applications.